Inside Front Cover: Switching between laser‐induced thermophoresis and thermal convection of liquid suspension in a microgap with variable dimension. Issue 21 (18th November 2021) - Tsuji, Tetsuro; Taguchi, Satoshi; Takamatsu, Hiroki
Abstract : DOI: 10.1002/elps.202100118 The cover picture shows the particle motion induced by laser‐induced thermal convection. Upon laser illumination to a microfluidic channel consisting of two parallel plates with proximity, a solution inside absorbs the light, generating internal heat. The resulting temperature field yields a buoyancy force acting on the fluid, which drives a microscale convective flow. This convection drags the dispersed particles, as shown in the image. Depending on the balance between the drag and thermophoretic forces, different spatial patterns of particles emerge in the channel.